(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
This paper aims to analyse the political role of the aristocracy in Liguria during the last twenty years of the Western Roman empire, from the death of Valentinian III to the reign of Julius Nepos in Italy (450‐475). During the final crisis of the imperial authority in the Western empire, the elites of Liguria resumed a significant political role. Firstly, as a consequence of his conflict with the emperor Anthemius in Rome, the patricius Ricimer ritired to Milan, where he held his court in 470/471. Some time later, after the deposition of Glycerius, the emperor Julius Nepos chose both Milan and Pavia (Ticinum) as residence and seat of his government. While Rome and the Italia Suburbicaria were under the political influence and control of the Roman senatorial aristocracy, Julius Nepos decided to stay in Italia Annonaria to lead the defence of the Gallic provinces against the Visigoths. Therefore, from summer 474 to summer 475 Milan and Lombardy were at the center of the political and diplomatic action of the last legitimate Western Roman emperor.